2006
DOI: 10.1111/j.1365-2591.2006.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐production of vascular endothelial cadherin and inducible nitric oxide synthase by endothelial cells in periapical granuloma

Abstract: Vascular endothelial-cadherin produced by endothelial cells could be regulated by iNOS-producing cells in periapical granulomas and might play a pivotal role in vascular permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
2
19
0
4
Order By: Relevance
“…the obtained results in this study are compatible with previously performed studies about iNOS-IR in PILs (10,11,22,23,24). One of the first studies revealing iNOS-IR presence in periapical tissues was performed by takeichi et al on radicular cysts.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…the obtained results in this study are compatible with previously performed studies about iNOS-IR in PILs (10,11,22,23,24). One of the first studies revealing iNOS-IR presence in periapical tissues was performed by takeichi et al on radicular cysts.…”
Section: Resultssupporting
confidence: 93%
“…Ca 2+ / calmodulin-independent type ii noS, also called macrophage noS or inoS isoform, is responsible for no production in development of Pils and is the most investigated type (2,10,11,22,23,24). However, it is not clear whether iNOS expression in PG and Rc groups differs between each other (11,10,23,24). iNOS may have an pivotal role in activation and proliferation of odontogenic epithelial components in DFs like in Pils progression.…”
Section: Introductionmentioning
confidence: 99%
“…The important effects of iNOS produced NO in pulpa (15), periapical tissue (19,21,37,38,39) and periodontal inflammatory lesions (1,20,24) have been shown. The iNOS based proliferative potential in epithelial tissues on periapical inflammatory lesions has been emphasized (37).…”
Section: Fig 1 Immunoreactivity For Inos In Denture Induced Fibrousmentioning
confidence: 99%
“…In the following research it has been reported that NO, being an important intercellular and extracellular messenger molecule, has both homeostatic functions like vasodilatation, neurotransmission, inhibition of platelet adhesion and aggregation, and also host defense functions against infectious agents such as bacteria, fungi and parasites, and tumor cells (29). Although NO is important in host defense and homeostasis, it is also regarded as harmful and has been implicated in the pathogenesis of a wide variety of inflammatory conditions (1,15,19,21,35,37,38,39). NO is synthesized by a group of isoenzymes collectively named NO synthase (NOS).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The interaction between RAGE and inducible nitric oxide by endothelial cells has also been studied, 25 and a possible role of these inflammatory mediators in tissue injury has been suggested. However, the interaction of RAGE with AGE or S100 in periapical periodontitis has not been assessed.…”
Section: Introductionmentioning
confidence: 99%